A importância dos exames neurológico e radiográfico no diagnóstico de lesões cervicais em equino: Relato de caso - Rivera, G. G. [UNESP]; Bueno, G. M. [UNESP]; Paula, V. B. [UNESP]; Santo, M. Q.P. [UNESP]; Matsui, A. [UNESP]; Escoba, A. [UNESP]; Vasconcelos, R. O. [UNESP]; Canola, J. C. [UNESP]; Canola, P. A. [UNESP]; Lacerda-Neto, J. C. [UNESP] (FapUNIFESP (SciELO), 2017)
Cervical vertebral lesions are relatively common in equine patients, but its diagnosis seems challenging for the clinician. Clinical signs most commonly associated with this clinical feature are paresis, paraplegia, tetraparesis, tetraplegia, which may lead the patient to a comatose state, and even death. Fortunately, these clinical signs can be perceived during physical examination. All of which, alongside imaging techniques, may allow a precise diagnose of the location of lesions and prediction of a prognosis for the patient. We present a case report of a Mangalarga mare, with four years of age, presenting signs of post-traumatic tetraplegia with spastic paralysis with increased muscular tonus and hyperreflexia in all four limbs. A thorough neurological examination of the patient associated with conventional and contrast medium radiographic imaging of the cervical region identified lesions at the atlas (C1) and axis (C2, and fifth (C5) and sixth (C6) cervical vertebrae. Fracture of the atlas vertebrae, dislocation of the axis' dens as well as subluxation of C5-C6 causing ventrodorsal medullary compression of the spinal cord were diagnosed radiographically. Due to the extent of the lesions the animal was euthanatized with the owner's consent. All lesions identified radiographically were posteriorly confirmed during post-mortem examination.
Fundamentals of neurological and radiographic examination on diagnosis of cervical lesions of a horse: Case report
Keywords: Equine; Fracture; Imaging; Medullary compression; Neck